MICROSCOPIC EVALUATION OF THE QUALITY OF DENTAL REPLACEMENT - Františka Pešlová; Daniela Koštialiková; Richard Veselý; Andrej Dubec; Maxim Puchnin (Acta Polytechnica CTU Proceedings)
The permanent tooth replacements including metal-ceramic crowns are a convenient solution for the renewing of the original function of the whole set of teeth as well as of the natural appearance. Development and preparation of suitable tooth replacement presents a real challenge for dental engineers as the replacement has to meet all the conditions and requirements of the dental medicine as well as patient’s needs and wishes. The preparation of the metal-ceramic crown is a sophisticated process and the dental engineer has to prepare alwaysa unique replacement on demand. In dental medicine there is a wide spectrum of inorganic and organic materials used formanufacturing of dental replacements. Each of the material has specific properties leading to distinct applications.Besides the material properties, the attention has to be paid to the aesthetic function and biocompatibility of the material to ensure thecomplete restoration of the whole set of teeth.